Chemical study of the San Antonio de Putina-Puno thermal water during the seasons of the year - Llahuilla Q., José A. (2020)
Thermomineral waters are traditionally used by the Peruvian population for various diseases. Objective: To determine and compare the chemical components of the thermal water of San Antonio de Putina-Puno during the seasons of 2017. Materials and methods: non-experimental design, carried out according to the recommendations included in section 1060B of Standard Methods for the Examination of Water and Wastewater in its 21 edition, Official Methods of Analysis of the Association of Official Analytical Chemists (AOAC) and US Standard (EPA). Metal concentrations were determined by Inductively Coupled Mass Spectrometry (ICP-MS) and nonmetals by ion chromatography (EPA 300.1993 rev.2.1) ANOVA was applied considering p <0.05 for significance. Results: 52 chemical components were analyzed in each season, and the most important are the average sodium 1604 mg / L, chloride 1,829.83 mg / L sulfate 763.97 mg / L and potassium 74.92 mg / L: the average concentration of total the chemical components in summer (85.23 mg / L), autumn (83.7mg / dL), winter (84.12mg / dL) and spring (82.67 mg / L), no significant differences were found between the values of each season. Conclusions: San Antonio de Putina-Puno thermal water has chemical elements with the highest concentration of sodium,